Strengthening institutional capacity for disaster management and risk reduction through climate-resilient agriculture - Babu, Suresh Chandra; De Pinto, Alessandro; Paul, Namita (International Food Policy Research Institute, 2019)
The frequency of natural disasters, especially storms and floods, has been increasing globally over the last several decades. Developing countries are especially vulnerable to such disasters but are often the least capable of coping with the associated impacts because of their limited adaptive capacity. Despite the increased interest in strengthening institutional capacity, it remains a challenge for many developing countries. Institutional capacity for disaster management and risk reduction can be built through various mechanisms. One key approach is via the agriculture sector, where climate-resilient agriculture has become an effective tool for adapting to climate change and developing resilience in the long run – resulting in increased capacity for disaster management and risk reduction at the system, institutional, and individual levels. This paper presents the experiences of four countries, which we have evaluated to develop an institutional strengthening framework.